MENINGKATKAN HASIL BELAJAR GERAK PASSING BAWAH BOLA VOLI MENGGUNAKAN MODIFIKASI PEMBELAJARAN MELALUI PERMAINAN LEMPAR TANGKAP PESERTA DIDIK KELAS VI UPT SDN 159 GRESIK - Hariyanto, Rudi Eko; Sapto Wibowo; M Rofi'i Zakaria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve learning outcomes in passing down through learning modifications using the game of throw and catch. The method used is classroom action research with two cycles. Each cycle includes planning, implementation, observation and reflection stages. The subjects of this research were class VI at UPT SDN 159 Gresik, which consisted of 14 students. In cycle I, the research results showed that 1 student reached the very good category, 4 students were in the good category, and 5 students were in the fair category, so that a total of 10 students were declared complete. A total of 4 students did not complete and were in the poor category. In cycle II, 2 students reached the very good category, 5 students in the good category, and 4 students in the sufficient category, so that 11 students were declared complete, and 3 students did not complete in the poor category. The average student score increased from 72.5% in Cycle I to 77.5% in Cycle II, showing an increase of 5%. The percentage of student learning completion increased from 71.4% in Cycle I to 78.5% in Cycle II, which shows an increase of 7.1%. In conclusion, the increase in average scores and student learning completion is influenced by the use of learning modifications through the game of catch, so that the learning process becomes more interesting and enjoyable.